Sustentabilidade como prática sociomaterial no processo de gerenciamento de um hotel em João Pessoa-PB - Silva, Laércio de Barros (2017)
Sustainability is a subject that has been continuously studied since the 1970s when it became a worldwide concern, not unlike Administration as a field of science has devoted equal attention to and focused on the thematic field of sustainability, especially in what concerns to study the impacts of organizational actions. This study focused on sustainability considerations in the hospitality sector. As a len of studies for the interpretation of the phenomenon it was used the approach of Practice-Based Studies (PBS), in particular the sociomateriality. The use of the sociomaterial approach is a manner of introducing new ways of seeing the phenomenon of sustainability through a more critical strand. Thus, studying sustainability through sociomateriality is to understand that it is not only formed by intentional human action but that the action of non-humans is also important for the realization of this practice. Thus, the general objective of this research was to understand how sustainability is given as a management practice in a hotel that declares itself sustainable in a brazilian Northeast capital city. The qualitative case study method was used to conduct the research using shadowing during the field observations and through interviews as well as informal conversations. As a way of analyzing the data, categories of analysis were established through the use of literature. Regarding the results, it is possible to affirm that sustainability is a sociomaterial practice and that it depends on the existence of nonhuman elements for its accomplishment. The categories of analysis were able to show that the sustainability that occurs in the hotel is very fragile, for which we make some recommendations for improvements regarding the possible practices. Still according to the results it is possible to affirm that sustainability is a non-prescriptive daily practice that emerges and perpetuates over time in a performative way. Finally, this research aimed to contribute to the advancement of management science in the theoretical and practical field of sustainability through real experiences.